CreativeLab_Sci&Math | A project for higher school innovation in science and mathematics - Cavadas, Bento (2018)
CreativeLab_Sci&Math ® is a project of the teachers of the Department of Mathematics and Natural Sciences of Polytechnic Institute of Santarém/School of Education. This project focuses in higher education innovation for teaching, learning and assessment in Science and Mathematics (S&M).